Comparative Efficiency of Different Fat Replacers to Develop Functional Low Fat Carabeef Cookies - Goswami, Meena; Sharma, B. D.; Mendiratta, S. K.; Pathak, Vikas; Sharma, Heena (Journal of Meat Science, 2019)
The present study was carried out to develop functional low fat carabeef cookies with incorporation of different fat replacers viz. Poppy  seeds, dried plum pulp powder and guar gum separately at 0.5-1.5% levels to replace 20-40% hydrogenated vegetable fat. The optimum  level of each fat replacer was selected as carabeef cookies incorporated with 0.5% poppy seeds powder to replacer 20% fat (PO), car abeef cookies incorporated with 1.5% guar gum powder to replace 40% fat (GT ) and carabeef cookies incorporated with 1.0% plum  pulp powder to replace 30% fat (PL). These selected levels of each fat replacer were further compared to select the best treatment Final  experiment was conducted to evaluate the comparative efficacy of these fat replacers on the basis of various physic-chemical properties  and sensory evaluation. There was significant difference (P
Keywords: Carabeef cookies; Fat replacers; Guar gum; Poppy seeds; Plum pulp powder; Consumer acceptance